1990
DOI: 10.1002/aic.690360505
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of gas‐agitated liquid‐liquid dispersions

Abstract: Gas-agitated liquid-liquid dispersions arise in applications as diverse as direct hydrogenation processes for bitumen and coal, and the manufacture of iron and steel. The transfer of gas-phase constituents to the dispersed liquid phase and /or elution of dispersed-phase drops have been identified as potential limiting phenomena in these processes. Consequently, mean drop size and drop size distribution are key design variables. In this paper, the impact of gas flux and the physical properties of dispersed-phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…They concluded that the addition of kerosene to water reduces the gas holdup, which is the same behavior observed when solid particles are added to gas-liquid systems. Hatzikiriakos et al (1990) reached the same conclusion in the experimental study of bubble columns whosi liquids were mixtures of water and organic compounds. Tht reduction in gas holdup has been attributed to the inc-ease in the apparent viscosity of the liquid (taken as a pseudosingle phase) due to the presence of dispersed drops.…”
supporting
confidence: 59%
“…They concluded that the addition of kerosene to water reduces the gas holdup, which is the same behavior observed when solid particles are added to gas-liquid systems. Hatzikiriakos et al (1990) reached the same conclusion in the experimental study of bubble columns whosi liquids were mixtures of water and organic compounds. Tht reduction in gas holdup has been attributed to the inc-ease in the apparent viscosity of the liquid (taken as a pseudosingle phase) due to the presence of dispersed drops.…”
supporting
confidence: 59%
“…Coulaloglou and Tavlarides (1977) descrïbed coalescence fiequency as the product of the collision efficiency and the coalescence efficiency. Hatzikiriakos et al (1990) presented a summary of collision frequency predictions, drop rupture and drop-drop coalescence in gas-agitated liquid-liquid dispersions. They noted that coalescence eficiency is assumed to be unity or less, and there is always a discrepancy between predicted and measured values.…”
Section: Konduru and Shaw 1990)mentioning
confidence: 99%
“…Also, aeration affects the droplet size distribution, thereby necessitating the study of emulsion droplet size on gas evolution. A significant amount of work has been presented in the literature to understand the phase interaction of liquid-liquid-gas systems for gas-agitated tanks. They observed that the gas bubbled through the emulsions leads to continuous droplet coalescence/breakup.…”
Section: Introductionmentioning
confidence: 99%